2019
DOI: 10.24853/elif.2.1.25-32
|View full text |Cite
|
Sign up to set email alerts
|

Blending Wattpad Platform and English Prose Course in Industrial Revolution Era 4.0

Abstract: This paper focuses on an exploration of Wattpad platforms and English prose course as blended learning models in undergraduate students. In the era of industrial revolution 4.0, the use of blended learning models is an alternative solution to the challenges of the times in integrating technological progress with learning. This study used descriptive qualitative research method to examine the concept of blending of wattpad platforms and English prose course. This research finding showed that wattpad platforms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…They enjoyed reading Wattpad by giving two response interpretive/reflective response and affective response. According to Rahman (2019), Digital reading is reading the texts from the technological medium such as the cellphones, tablets, or computers either online or offline. Therefore, Wattpad is easier to access because can support them to read short stories anywhere.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They enjoyed reading Wattpad by giving two response interpretive/reflective response and affective response. According to Rahman (2019), Digital reading is reading the texts from the technological medium such as the cellphones, tablets, or computers either online or offline. Therefore, Wattpad is easier to access because can support them to read short stories anywhere.…”
Section: Discussionmentioning
confidence: 99%
“…There are so many studies that use Wattpad as a media to learning literature. Rahman & Iwan (2019) found that the Wattpad platform can be used to publish literary works students in the form of prose to further obtain constructive peer to peer feedback. Similar to Rahman and Iwan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Students are required to not only study literary works, but also to compose and present their own works in order to exercise their evaluative and appreciating talents. One of the practical options for students and lecturers to have active contact both face to face and online is to use blended learning through the Wattpad platform media (Rahman & Iwan, 2019).…”
Section: Introductionmentioning
confidence: 99%